(untitled) (Studia Prawnicze / The Legal Studies, 1983)
A relation between legal norms and morality is manifested especially in the field of farnlly law. The autor discusses this problem, with regard to obligation of alimony, taking into consideration the question of admissibility of application to those claims of art. 5 of the civil code. The work presents court decisions and opinions of representatives of law on the refusal to fulfil an obligation of alimony considering the fact that the claims are contrary to the principles of social coexistance. The author says that it is a controversial question but opinions in favour of that objection in cases when the person claiming alimony is deserving of moral condemnation have been more and more often pronounced. The author also oppugns an opinion that property sanction cannot be applied for failure to fulfil an obligation of a non-property character because the violation of the principles of social coexistance also concerns blameworthy behaviour in the sphere of non-property relations. The author oibjects to the adjudication of claims for alimony disregarding their moral aspect and points to ,different regulation of this problem in legislation of many other countries, boa socialist and capitalist ones. An attempt to work out certain instructions in the field of application of art. 5 of the civil code towards claims for alimony has been preceeded by remarks on norms and moral valuation, especially on the basis of dominant moral doctrines. Eventually, fundamental moral postulates formulated by various moral doctrines, and first of all by Marxist and Christian doctrines, turn out ,to be similar, although based on different ideological assumptions. The author presents typology of behaviours a negative moral evaluation of which should exert influence on legal appraisal of claim for alimony and, finally, may result in absolute refusal of legal protection of that claim, having applied art. 5 of the civil code.